Relevansi Teologi Kovenan dalam Pemberitaan Injil dan Implikasinya Terhadap Pembinaan Rohani Jemaat - Nasrul Nasrul; Daniel Pesah Purwonugroho; Didit Yuliantono Adi (Sekolah Tinggi Teologi Immanuel Sintang Kal-Bar, 2025)
This paper is designed to explore the relevance of covenant theology in the preaching of the gospel and its implications for the spiritual formation of the church. Covenant theology is a theology derived from the Bible. Covenant theology frames God's interaction with humans through the lens of covenant. The gospel affirms God's saving power. The proclamation of the gospel has vital urgency in the church. The intersection of covenant theology and the gospel is in the person of Jesus Christ and His perfect work of redemption. By understanding covenant theology in the preaching of the gospel, the congregation will understand the richness of God's promises centered on Jesus Christ. Through a descriptive qualitative approach, the author tries to pay attention to the relevance of covenant theology in the preaching of the gospel in the spiritual life of the congregation. The author asserts that the preaching of the gospel is very relevant to covenant theology because the meeting point of both is in the person and work of Jesus Christ. The relevance of covenant theology in the preaching of the gospel will have a positive and constructive impact on the spiritual development of the congregation. This paper offers a new perspective on the preaching of the gospel from the perspective of covenant theology to foster the spiritual life of the congregation.